Women's Experiences of Adult Sexual Assault, by Perpetrator Gender and Participant Sexual Orientation. - MacDonald, Alyssa J.; Holmberg, Diane; Price, E. Lisa; Hoskin, Rhea Ashley (Journal of Interpersonal Violence, 2025)
The vast majority of theoretical and empirical research assessing sexual assault (SA) focuses on man-against-woman SA (MWSA), leaving other forms such as woman-against-woman SA (WWSA) understudied. Relatively simple questions, such as the relative frequency of WWSA for women of different sexual orientations, the tactics (e.g., coercion, force), or forms (e.g., groping, vaginal penetration) employed in WWSA remain unanswered. To address these issues, 268 women (approximately one-third of each bisexual, lesbian, and heterosexual) completed an online survey reporting on whether or not they had experienced a variety of nonconsensual sexual experiences in their adult lifetime, asking specifically about perpetration by men and women. Results indicated that although SA perpetrated by men was far more common, a substantial minority of participants reported having experienced WWSA. In general, tactics and forms employed were similar, regardless of the gender of the perpetrator or the woman's sexual orientation, with two exceptions: bisexual women had experienced higher rates of MWSA, and lesbian women had experienced more SA in the form of oral sex compared to other groups. Implications for theory, empirical research, and especially community and clinical practice are discussed.